Decline and Renewal: Causes and Cures of Decay among Foreign-Trained Intellectuals and Professionals in the Third World. - Hendrickson, Harvey S. (The Accounting Review, 1987)
Reviews the book 'Decline and Renewal: Causes and Cures of Decay Among Foreign-Trained Intellectuals and Professionals in the Third World,' by Craufurd D. Goodwin and Michael Nacht.